Frameless Stereotactic Radiosurgery on the Gamma Knife Icon: Early Experience From 100 Patients. Issue 4 (2nd August 2019) - Vulpe, Horia; Save, Akshay V; Xu, Yuanguang; Elliston, Carl D; Garrett, Matthew D; Wu, Cheng-Chia; Cheng, Simon K; Jani, Ashish H; Bruce, Jeffrey N; McKhann, Guy M; Wang, Tony J C; Sisti, Michael B
Abstract: BACKGROUND: The Gamma Knife (GK) Icon (Elekta AB) uses a cone-beam computed tomography (CBCT) scanner and an infrared camera system to support the delivery of frameless stereotactic radiosurgery (SRS). There are limited data on patients treated with frameless GK radiosurgery (GKRS). OBJECTIVE: To describe the early experience, process, technical details, and short-term outcomes with frameless GKRS at our institution. METHODS: We reviewed our patient selection and described the workflow in detail, including image acquisition, treatment planning, mask-based immobilization, stereotactic CBCT localization, registration, treatment, and intrafraction monitoring. Because of the short interval of follow-up, we provide crude rates of local control. RESULTS: Data from 100 patients are reported. Median age is 67 yr old. 56 patients were treated definitively, 21 postoperatively, and 23 had salvage GKRS for recurrence after surgery. Forty-two patients had brain metastases, 26 meningiomas, 16 vestibular schwannomas, 9 high-grade gliomas, and 7 other histologies. Median doses to metastases were 20 Gy in 1 fraction (range: 14-21), 24 Gy in 3 fractions (range: 19.5-27), and 25 Gy in 5 fractions (range: 25-30 Gy). Thirteen patients underwent repeat SRS to the same area. Median treatment time was 17.7 min (range: 5.8-61.7). We found an improvement in our workflow and a greater number of patients eligible for GKRS because of the ability to fractionate treatments. CONCLUSION: We report a large cohort of consecutive patients treated with frameless GKRS. We look forward to studies with longer follow-up to provide valuable data on clinical outcomes and to further our understanding of the radiobiology of hypofractionation in the brain. Graphical Abstract: